Barriers to Handicraft Development in Rural Saravan, Iran: A Bayesian Network and Fuzzy AHP Analysis (Indian Journal of Extension Education, 2025)
The study examined the key barriers hindering the development of the handicraft sector in Saravan, Iran, with a focus on identifying their significance and interrelationships. Despite the global recognition of Saravan’s Kalporagan pottery, a 7,000-year-old tradition preserved by local women, the region’s handicraft industry has faced persistent stagnation. A mixed method approach was adopted, utilizing the Fuzzy Analytical Hierarchy Process (FAHP) to categorize barriers into six main groups: managerial, motivational-psychological, marketing and sales, financial-economic, skill-technical, and product-based. This study was conducted in 2024. The findings showed that managerial barriers were the most critical, followed by motivational and marketing challenges, while product-related barriers had the least impact. To explore causal connections among these barriers, Bayesian Network Analysis (BNA) was applied, revealing that managerial shortcomings significantly influenced financial and marketing constraints. The study concluded that addressing managerial inefficiencies could alleviate other development obstacles. It emphasized the need for targeted institutional reforms, investment in tourism infrastructure, and improved market access to revitalize Saravan’s handicrafts and contribute to sustainable rural development.